THE IMPACT OF LIQUIDITY RATIO, LEVERAGE RATIO, COMPANY SIZE AND AUDIT QUALITY ON GOING CONCERN AUDIT OPINION - Kumalawati Abadi; Din Mukhlis Purba; Qonita Fauzia (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
The main purpose of this study to analyze liquidity ratio, leverage ratio, company size, and audit quality ongoing concern opinion. The logistic regression analysis model is used to identify the effect of independent variables on the dependent variable. The sample is taken from the manufacturing company listed on the Indonesia Stock Exchange. The data covers a period of three years, from 2015 to 2017. The results of this study leverage and audit quality variables have a significant positive effect ongoing concern audit opinion, while other variables such as liquidity proxied by the current ratio, leverage proxied by the debt to equity ratio and company size are insignificant ongoing concern audit opinion.